EXPLORE: A Prospective, Multinational, Natural History Study of Patients with Acute Hepatic Porphyria with Recurrent Attacks - Gouya, Laurent (Hepatology, 2019)
BACKGROUND AND AIMS: Acute hepatic porphyria comprises a group of rare genetic diseases caused by mutations in genes involved in heme biosynthesis. Patients can experience acute neurovisceral attacks, debilitating chronic symptoms, and long‐term complications. There is a lack of multinational, prospective data characterizing the disease and current treatment practices in severely affected patients. APPROACH AND RESULTS: EXPLORE is a prospective, multinational, natural history study characterizing disease activity and clinical management in patients with acute hepatic porphyria who experience recurrent attacks. Eligible patients had a confirmed acute hepatic porphyria diagnosis and had experienced ≥3 attacks in the prior 12 months or were receiving prophylactic treatment. A total of 112 patients were enrolled and followed for at least 6 months. In the 12 months before the study, patients reported a median (range) of 6 (0‐52) acute attacks, with 52 (46%) patients receiving hemin prophylaxis. Chronic symptoms were reported by 73 (65%) patients, with 52 (46%) patients experiencing these daily. During the study, 98 (88%) patients experienced a total of 483 attacks, 77% of which required treatment at a health care facility and/or hemin administration (median [range] annualized attack rate 2.0 [0.0‐37.0]). Elevated levels of hepatic δ‐aminolevulinic acid synthase 1 messenger ribonucleic acid levels, δ‐aminolevulinic acid, and porphobilinogen compared with the upper limit of normal in healthy individuals were observed at baseline and increased further during attacks. Patients had impaired quality of life and increased health care utilization. CONCLUSIONS: Patients experienced attacks often requiring treatment in a health care facility and/or with hemin, as well as chronic symptoms that adversely influenced day‐to‐day functioning. In this patient group, the high disease burden and diminished quality of life highlight the need for novel therapies.